Lemmus amurensis Vinogradov 1924 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Lemmus amurensis Vinogradov, 1924. Ann. Mag. Nat. Hist., ser. 9, 14:186. TYPE LOCALITY: Siberia, Pikan, on River Zeya, a tributary of the Amur River. DISTRIBUTION: Larch taiga of E Siberia, from east of Lake Baikal through the upper Amur River basin, and north in the Verkhoyansk and Cherskogo Mtns to the River Omolon (see Chernyavskii et al., 1980). SYNONYMS: ognevi. COMMENTS: A distinctive species revised by Chernyavskii et al. (1980). Additional chromosomal data analyzed by Gileva et al. (1984) in context of distinguishing species of Lemmus. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 516, DOI: 10.5281/zenodo.7353098